Efektivitas Penggunan Teknologi Informasi Dalam Meningkatkan Kualitas Pelayanan Publik (Studi Pada Aplikasi Poedak di Dispenduk Capil Kabupaten Gresik) - Yanti Nabilla, Clarizah Rizki; Prastyawan, Agus (Universitas Negeri Surabaya, 2023)
The purpose of this study is to determine the effectiveness of the Poedak application program that has been running so far. The research method used in this study is descriptive qualitative by describing phenomena or events that occur in the field. The research focus is related to the effectiveness of the Poedak application program using Budiani's theory (program objectives, program outreach, program objectives, and program monitoring) and the implementation of services using the Poedak application, including the supporting and supporting factors. In connection with the introduction of a new public service by the Government of Gresik Regency, namely poedak application, the purpose of this research is to conduct a qualitative phenomenological research. Interviews, direct observation, and written notes were used as data collectors. Methods for analyzing data include collecting information, synthesizing it, presenting it, and checking assumptions based on the data. As in the socialization of the program that is carried out less optimally. Through the research process carried out, several suggestions were found that researchers could provide, namely by optimizing the socialization of the Poedak application program to the public, adding information on the official Disdukcapil website about the Poedak application program, and clarifying procedures and administrative rules related to filing services online. Keywords: Efectiveness, Poedak Application, Public Service